Essential oils and fatty acids of Stachys L. taxa, a chemotaxonomic approach - Kiliç, Ömer; Özdemir, Fethi Ahmet; Yildirimli, Şinasi (Progress in Nutrition, 2017)
The aerial parts and seeds of ten Stachys L. taxa were investigated for their essential oil and fatty acid composition. Linanyl acetate, α-terpineol, germacrene D, β-myrcene, α-pinene, linalool, caryophyllene oxide, β-caryophyllene, spathulenol were detected as the major components of the essential oils. Almost all Stachys taxa have the same fatty acid pattern, except for minor differences. The most abundant components were linoleic, oleic and palmitic acid. A cluster analysis was carried out for comparison and characterisation of the seed and essential oil from the Stachys taxa.